Kesiapan Guru Mengenalkan Budaya Betawi dalam Pembelajaran di Taman Kanak-Kanak: Tinjauan pada Penerapan Kurikulum Merdeka - Rohita (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Introducing culture through the learning process to early childhood requires readiness from educators. The purpose of this research is to describe how the teacher's readiness to introduce Betawi culture in learning in Kindergarten. The research was conducted using qualitative methods with a case study approach. Respondents were 2 people consisting of school principals and teachers. Data collection was carried out using open interview methods, observation of the learning process, and documentation. Data analysis was carried out using the Milles and Hubberman model with 4 steps, namely data collection, data reduction, data presentation, and drawing conclusions/verification. The results of the study show that although teachers still need to improve their understanding of the Merdeka Curriculum, teachers are ready to introduce Betawi culture to children, especially the I Love Indonesia theme with the topic Es Selendang Mayang. Readiness can be seen from the selection of materials, preparation of teaching materials, and mastery of teaching materials, where this occurs, among other things, due to the teacher's critical reflection and the collaboration of school principals, teachers, and parents. The implication is the need for collaboration between teachers, principals, and parents in introducing local culture as the implementation of the Independent Curriculum; as well as increasing teacher knowledge about local culture so that they can master the material that will be presented while at the same time being able to create a learning environment that is in accordance with the local cultural material.